FROM CAPTIVE TO NON-CAPTIVE: LEVERAGING VERTICAL INTEGRATION FOR MARKET EXPANSION AT PT. PETRO ENERGY - Lailly Novila Hakim; Harimukti Wandebori (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines PT. Petro Energy, a captive fuel trading company in Indonesia facing critical revenue concentration risk, with over 95% of revenue derived from related-party customers in the coal mining sector. Following a vertical integration merger with PT. Storindo effective January 1, 2025, the company gained direct control of 85,000 KL storage infrastructure, transforming its cost structure from variable to fixed costs and raising operating leverage. This research develops a comprehensive strategic framework for market expansion into non-captive customer segments, combining industrial organization and Resource-Based View (RBV) perspectives. Analytical tools include VRIO analysis, Value Chain Analysis, PESTEL, Porter's Five Forces, STP, Marketing Mix 4Ps, SWOT-TOWS matrix, McKinsey 7S, and Kotter's 8-Step Change Model. Primary data was collected through in-depth interviews with the Board of Directors, management, and key captive customers, supported by quantitative financial ratio analysis from 2022–2024 audited financial statements. Findings reveal strong financial readiness (Current Ratio 8.97x, Gross Margin 43%, low Debt-to-Equity of 0.12) but urgent need to address declining Asset Turnover (0.99x) and lengthening Cash Conversion Cycle (90 days). A focused differentiation strategy targeting non-captive mining and construction segments, leveraging Fuel-as-a-Service (FaaS) capability and extended credit terms, is proposed alongside a phased organizational transformation roadmap.